Quantitative Strategic Planning Matrix (QSPM) Analysis to Determine the Performance Recovery Strategy of the Processing Industry to Support the Green Economy Policy in East Java - Alvin Prasetyo; Mochamad Devis Susandika (Universitas Yudharta Pasuruan, 2022)
The processing industry in East Java experienced a contraction due to the COVID-19 pandemic. The purpose of this research is to evaluate the performance of the processing industry and determine a strategy for recovering the performance of the processing industry to support the green economy policy in East Java. The analysis tool uses quantitative strategic planning matrix analysis. The results of the analysis are increasing cross-sectoral commitment and coordination, increasing collaboration with multi-stakeholders, improving governance of green industry programs, active communication, increasing campaigns and socialization related to green industry, increasing multi-stakeholder capacity, building a good mindset in industrial society, increasing cross-sectoral roles, and improve the performance of the processing industry. The East Java Provincial Government is expected to carry out several strategies for the development of green industries, with the following strategic sequence: increasing cross-sectoral commitment and coordination, increasing collaboration with multi-stakeholders, improving governance of green industry programs, active communication, increasing campaigns and socialization related to green industries, increasing multi-stakeholder capacity, build a good mindset in the industrial community, increase cross-sectoral roles, and improve the performance of the manufacturing industry.